Sliding Mode Control for a Gyroscope System - Izabela KRZYSZTOFIK (Sterowanie ślizgowe układem giroskopowym, 2017)
This paper presents a mathematical model of a gyroscope system with a sliding mode controller. A comparative analysis based on various control algorithms implemented in a controlled gyroscope system installed on a mobile platform (such as an UAV or a homing rocket missile) proved that sliding mode control can be highly effective, especially when external input interferences exist with the kinematic reactions of the mobile platform. A gyroscope system with a sliding mode controller can be used in the optical target seeker systems of precision weapons. The simulation results are provided in a graphical format.
Keywords: Sterowanie układem giroskopowym